Pengelolaan Pajak Bumi dan Bangunan di Kecamatan Bangkala Barat Kabupaten Jeneponto - Andi Pattarani (Universitas Muhammadiyah Makassar, 2018)
This study aims to; 1) tofind out the effectiveness of the implementation of land and building tax collection carried out in West Bangkala District, Jeneponto Regency. , 2) uto know all the problems that arise in the implementation of the Land and Building Tax and 3) uto know whether the target of the Land and Building Tax is achieved or not. Especially in increasing development financing. The data analysis method used in this study is a qualitative descriptive analysis method. The results showed that: 1) the implementation of land and building tax collection in the West Bangkala district of Jeneponto Regency has been effective, 2) there are several obstacles in the implementation of the Land and Building Tax, namelythat there are taxpayers who are in arrears with their tax debts; kis the perfectness of tax administration; and sometimesthe collection time is not right 3) the land and building tax target in West Bangkala district, Jeneponto Regency has exceeded the target.